Peran Komunikasi Inovasi Koperasi Wanita dalam Penguatan Ekonomi Perempuan Madura: Studi Kasus Koperasi Nadhliyatun Nisa’ Sumenep - Salzafira Al Madinah MF; Sayyidil Akbar; Farida Nurul Rahmawati (Penerbit Widina, Widina Media Utama, 2025)
Cooperatives are considered a strategic tool to achieve the Sustainable Development Goals (SDGs), particularly poverty alleviation and gender equality. Women's cooperatives in rural areas of Indonesia play an important role in strengthening women's micro, small, and medium enterprises (MSMEs) as well as improving family economies. However, women's cooperatives still face many challenges, especially those related to social, cultural, and economic factors, as well as limitations in utilizing innovative and communication technologies to develop businesses and marketing. Nadhliyatun Nisa' Cooperative in Kebon Agung Village, Sumenep Regency, Madura, is used to evaluate the role of innovation communication in strengthening women's cooperatives. The study was conducted using a qualitative approach, involving documentation, in-depth interviews, and observation. Research shows that cooperatives help members improve by providing skills training such as business management, marketing strategies, and financial literacy. Innovation communication is very important to support members' economic resilience, expand business networks, and enhance the competitiveness of local products. This cooperative has successfully increased members' income, entrepreneurial skills, and women's social standing in the community, despite facing various structural and cultural challenges.ABSTRAKKoperasi dianggap sebagai alat strategis untuk mencapai Tujuan Pembangunan Berkelanjutan (SDGs), terutama pengentasan kemiskinan dan kesetaraan gender. Koperasi wanita di wilayah pedesaan Indonesia memainkan peran penting dalam memperkuat usaha mikro, kecil, dan menengah (UMKM) perempuan serta meningkatkan perekonomian keluarga. Namun, koperasi wanita masih menghadapi banyak masalah, terutama yang berkaitan dengan faktor sosial, budaya, dan ekonomi, serta keterbatasan dalam menggunakan inovasi dan komunikasi teknologi untuk mengembangkan usaha dan pemasaran. Koperasi Nadhliyatun Nisa' di Desa Kebon Agung, Kabupaten Sumenep, Madura, digunakan untuk mengevaluasi peran komunikasi inovasi dalam penguatan koperasi wanita. Penelitian dilakukan dengan pendekatan kualitatif, yang melibatkan dokumentasi, wawancara mendalam, dan observasi. Penelitian menunjukkan bahwa koperasi membantu anggota menjadi lebih baik dengan memberikan pelatihan keterampilan seperti manajemen usaha, strategi pemasaran, dan literasi keuangan. Komunikasi inovasi sangat penting untuk mendukung ketahanan ekonomi anggota, memperluas jaringan usaha, dan meningkatkan daya saing produk lokal. Koperasi ini telah berhasil meningkatkan pendapatan anggota, keterampilan kewirausahaan, dan posisi sosial perempuan dalam komunitas, meskipun menghadapi berbagai tantangan struktural dan kultural.